Mobile-based climate services impact on farmers risk management ability in India - Mittal, Surabhi; Hariharan, Vinod K. (Elsevier, 2018)
The climate service advisory was piloted in two states of India – Haryana and Bihar – covering 46 villages. Households were randomly selected in these villages to receive voice-based messages on individual farmers’ mobile phones during the project period 2013–2015. The messages had content related to weather, seed varieties, climate-smart agricultural practices (CSAPs), efficient utilization of agricultural inputs, pests, and weed and nutrient management. In this context, this paper analyzes the listening rate of the messages by the individual farmers over the span of two years. The paper also analyzes and describes the process of change of farmers’ ability to use the information in the messages to improve the awareness and then further convert the information into economic gains. The paper does so in the framework of a conceptual model that highlights the process of change – information use, if facilitated by enabling factors, has the potential to create outputs which can be measured as benefits (monetary and change in level of awareness). It is believed that mobile-phone enabled agro-advisory services have the potential to reduce information gaps and generate awareness about improved technologies which leads to improved adoption of technology. Through the pilot study, we show how climate services helped in enhancing farmers’ awareness about the CSAPs.